Benefits of Animated Video on Oral Hygiene for Children with Autism Spectrum Disorders (A Study of Difficulty Factors in Oral Hygiene) (Dentika: Dental Journal, 2025)
This quasi-experimental study used a single-group pretest/posttest design to evaluate the effectiveness of an animated video intervention on oral hygiene behaviors among 34 children with Autism Spectrum Disorder (ASD). The animated educational video was administered 15 times over five weeks. Data were collected using parental questionnaires and observational checklists. Significant improvements in oral hygiene maintenance behaviors were observed post-intervention. The results showed that 91.18%, 94.12%, and 85.29% of participants brushed twice daily, used fluoride toothpaste, and reduced soft drink consumption, respectively. The Wilcoxon signed-rank test confirmed statistically significant positive changes in five out of seven measured behaviors (p